2022
DOI: 10.1001/jamaneurol.2022.0489
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maintenance Intravenous Immunoglobulin With Prevention of Relapse in Adult Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disease

Abstract: IMPORTANCE Recent studies suggest that maintenance intravenous immunoglobulin (IVIG) may be an effective treatment to prevent relapses in myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD); however, most of these studies had pediatric cohorts, and few studies have evaluated IVIG in adult patients.OBJECTIVE To determine the association of maintenance IVIG with the prevention of disease relapse in a large adult cohort of patients with MOGAD. DESIGN, SETTING, AND PARTICIPANTSThis was a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
2
39
0
2
Order By: Relevance
“…The risk of relapse was lower in those treated with higher IVIG doses or more frequently (e.g., 0.4 g/kg every week, or 2 g/kg every 4 weeks). Two patients (3%) experienced worsening disability (EDSS score) during IVIG treatment (167). The high costs and restricted availability are the main elements that limit the use of this treatment in a larger scale.…”
Section: Maintenance Treatmentmentioning
confidence: 99%
“…The risk of relapse was lower in those treated with higher IVIG doses or more frequently (e.g., 0.4 g/kg every week, or 2 g/kg every 4 weeks). Two patients (3%) experienced worsening disability (EDSS score) during IVIG treatment (167). The high costs and restricted availability are the main elements that limit the use of this treatment in a larger scale.…”
Section: Maintenance Treatmentmentioning
confidence: 99%
“…The use of IVIG is more common in other CNS demyelinating diseases, such as MS, as compared to MOG-AD. Olyaeemanesh et al ( 21) performed a meta-analysis including six randomized (24) showed that maintenance IVIG was effective in reducing relapses. To date, IVIG has not been considered as a firstor second-line therapy for MOG-AD due to insufficient clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…large sample sizes and a lack of comparative groups were not included, for example, Ringelstein et al (33) found blocking IL-6R was safe and effective in treating MOG-AD; Chen et al and Hacohen et al (24) recently performed a multicenter cohort study and confirmed the efficacy of IVIG in treating MOG-AD; therefore, the exclusion of single-arm studies may exaggerate or underestimate the efficacy of certain treatments. Third, the definite therapeutic efficacy could not be assessed due to the combination of immunosuppressors with OC in some studies, and many of the studies have included patients more than once if they have been on multiple treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term treatment is recommended for patients at risk for relapse and current therapies comprise the off-label use of prednisolone, steroid-sparing immunosuppression with azathioprine, methotrexate, mycophenolate mofetil, rituximab and IVIG [75][76][77][78][79]. Maintenance treatment is given either as monotherapy or as combination therapy [9,38,42].…”
Section: Accepted Manuscriptmentioning
confidence: 99%